A review of the Hangingflies (Mecoptera: Bittacidae) of South Asia with the description of a new species of Bittacus from Nepal - Bicha, Wesley J. (Zootaxa, 2011)
A new species of hangingfly, Bittacus coheri, is described from the eastern Terai of Nepal. The male of this species differs from all other known south Asian hangingflies by the presence of a bifurcated flap-like structure between the male epiandrial lobes of tergum 9. Bittacus taraienseis Penny is placed in synonymy with B. indicus Walker, leaving south Asia (Iran to Bangladesh) with six species of hangingflies: at least two with West African affinities and at least two with oriental affinities. Additional records of B. nodosus and B. henryi are given.